Diabetes mellitus: what the neurologists need to know. Issue 6 (30th July 2022) - Stephens, Jeffrey Wayne; Williams, David M; Chudleigh, Richard
Abstract : Diabetes mellitus is a common condition associated with numerous complications and comorbidities. The diabetes spectrum includes type 1, type 2 and other forms of diabetes, which may be associated with medical therapies and genetic factors. Type 2 diabetes is managed with lifestyle, oral therapies, non-insulin-based injectables and subsequently insulin. Type 1 diabetes requires insulin from the time of diagnosis. In recent years, there have been considerable developments in the therapies available to treat type 2 diabetes and some of these also afford cardiorenal protection. This review summarises the nature, complications and therapeutic advances in the field of diabetes and provides a concise review for neurologists. Managing diabetes optimally prevents complications and all medical specialties need a basic understanding of the principles involved in diabetes care.